Sampling frequency impacts the measurement of walking activity after stroke - Knarr, Brian (J Rehabil Res Dev, 2013)
The purpose of this study was to examine the effect of sampling epoch on total time spent walking and number of walking bouts/day in persons with stroke. 98 persons post-stroke with average age of 63.8±10.3 years and 43.6±58.1 months post-stroke participated in this study. Participants wore a StepWatch Activity Monitor (SAM) for 3–5 consecutive days. The number of strides taken was collected in consecutive 5 second epochs and down sampled into 10, 20, 30, and 60 second epochs. Total time walking and total number of walking bouts were determined for each day. Low and high activity days were determined as days below and above the 25(th) and 75(th) percentile of total steps/day, respectively. Total time walking and total number of bouts were different for each sampling epoch (p<0.001 for all). The 5 second sampling epoch resulted in calculation of ~40% of the walking time and ~6 times as many bouts as a 60 second sampling epoch. Differences were greater for low activity days (p<0.001 for all). Sampling epoch affects the calculation of daily step activity variables whose calculation depends on time, especially during low activity days. Sampling epoch must be carefully considered when designing studies aimed at understanding patterns of daily walking activity.